STAT3 couples activated tyrosine kinase signaling to the oncogenic core transcriptional regulatory circuitry of anaplastic large cell lymphoma - Prutsch, Nicole; He, Shuning; Berezovskaya, Alla; Durbin, Adam D; Dharia, Neekesh V; Maher, Kelsey A; Matthews, Jamie D; Hare, Lucy; Turner, Suzanne D; Stegmaier, Kimberly; Kenner, Lukas; Merkel, Olaf; et al. (Cell reports. Medicine, 2024)
Anaplastic large cell lymphoma (ALCL) is an aggressive, CD30+ T cell lymphoma of children and adults. ALK fusion transcripts or mutations in the JAK-STAT pathway are observed in most ALCL tumors, but the mechanisms underlying tumorigenesis are not fully understood. Here, we show that dysregulated STAT3 in ALCL cooccupies enhancers with master transcription factors BATF3, IRF4, and IKZF1 to form a core regulatory circuit that establishes and maintains the malignant cell state in ALCL. Critical downstream targets of this network in ALCL cells include the protooncogene MYC, which requires active STAT3 to facilitate high levels of MYC transcription. The core autoregulatory transcriptional circuitry activity is reinforced by MYC binding to the enhancer regions associated with STAT3 and each of the core regulatory transcription factors. Thus, activation of STAT3 provides the crucial link between aberrant tyrosine kinase signaling and the core transcriptional machinery that drives tumorigenesis and creates therapeutic vulnerabilities in ALCL.
Keywords: signální transdukce; Adult; Janus Kinases; lidé; Signal Transduction; Humans; Child; Lymphoma, Large-Cell, Anaplastic; anaplastická lymfomová kináza; Carcinogenesis; transkripční faktory STAT; transkripční faktor STAT3; anaplastický velkobuněčný lymfom; karcinogeneze; Cell Transformation, Neoplastic; dospělí; dítě; nádorová transformace buněk; Janus kinasy; STAT Transcription Factors; Anaplastic Lymphoma Kinase; STAT3 Transcription Factor